Effect of Torrefaction Pretreatment on Combustion Behavior of Different Agricultural Wastes - Duranay, Neslihan; Yilgin, Melek; Aydogmus, Ercan (Mehmet Sinan Bilgili, 2022)
In this study, which was carried out to investigate the effect of the torrefaction process on the combustion behavior of agricultural wastes, the outer and inner shells of almonds, olive seeds, and corn stalks were used as agricultural waste. Torrefaction was applied to the samples dried in a laboratory atmosphere for 41 minutes at 300 +/- 5 degrees C. The change in fuel properties was determined by making proximate analyzes of the solid product obtained after the process and compared with the raw sample. The effects of the torrefaction process on the combustion behavior of agricultural wastes of different structures were investigated by burning the 1 +/- 0.15 weighted raw and solid product samples at 700 degrees C furnace initial temperature in a fixed bed system. Obtained results showed that solid fuel similar to coal can be produced by the torrefaction process applied to agricultural wastes and it can be burned instead of coal or mixed with coal in coal-fired systems. Thus, it will both contribute to the national economy and add value to waste that causes problems in storage and transportation.
6th EurAsia Waste Management Symposium (EWMS) -- OCT 24-26, 2022 -- Istanbul, TURKEY
Keywords: Agricultural waste; torrefaction; combustion; energy recovery